Difference Results Bacteria Numbers with Variations Temperature and Check Time in The Elderly Urine Suspect Urinary Tract Infections (UTI) - Septiani, Risma Dyah; Silviani, Yusianti (Jurnal Biologi Tropis, 2024)
Delays in examination have the potential to result in differences in the results of the number of bacteria in the examined specimens plus storage of specimens at non-optimal temperatures. The difference in the number of bacteria can be known by examining the Total Plate Count (TPC) in urine. The purpose of this study was to determine the differences in the results of germ numbers in terms of variations in examination delays and urine storage temperatures of elderly suspects with urinary tract infections (UTI).  The type of research conducted was experimental analytic with the subject of 4 elderly urine in Kratonan Village, Surakarta with criteria sampling technique. Research data were obtained through questionnaires and examination of total plate numbers with mayo technique examination, where the results were multiplied by a conversion factor of 102 CFU/ml.  The results were analyzed by SPSS statistical test using Two Way ANOVA which obtained a significant value of 0.915 (p>0.05). Then continued with SPSS data analysis using Tukey Pos Hoc aims to see the real difference of each variation. There is no difference in the germ count results with temperature variations and time delays in the urine of elderly suspected urinary tract infection (UTI) patients.